Resolution of taxonomic ambiguity in groupers (Pisces: Serranidae) by the random amplified polymorphic DNA (RAPD) technique - Roy, T. S. C.; Gopalakrishnan, A.; Muneer, P. M. A.; John, L.; Musammilu, K. K.; Basheer, V. S. (Indian Journal of Fisheries, 2014)
In this study, a species specific molecular marker RAPD (Random Amplified Polymorphic DNA) was used for resolving taxonomic ambiguity in groupers thereby helping in species identification. Fishes were collected from the coast of Mandapam and Keelakkarai, Tamil Nadu. RAPD patterns were developed for 8 species of groupers and each one had a unique RAPD profile. The phylogenetic relationships of these species were also analysed.